RETRACTED: Treatment mechanism of hexavalent chromium wastewater in constructed wetland-microbial fuel cell coupling system - Shi, Yucui; Tang, Gang; You, Shaohong; Jiang, Pingping; Zhang, Xuehong; Deng, Zhenliang (Frontiers in Environmental Science, 2022)
Cr(VI) is toxic to the human body and environment. As a suitable wastewater treatment with low energy requirement technology, constructed wetland-microbial fuel cells (CW-MFCs) can treat Cr(VI) wastewater while generating electricity. In this study, CW-MFC and constructed wetland systems were developed to purify Cr(VI) wastewater. The removal mechanism of Cr(VI) was examined by electron paramagnetic resonance (EPR), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectroscopy. The results demonstrated that the average pollutant removal efficiency of the CW-MFC system is 2.99%–8.13% higher than that of the constructed wetland system, and the maximum power density is 505.61 mW·m−2. Moreover, the XPS and EPR analyses demonstrated that Cr in substrates and Leersia hexandra Swartz primarily is in the form of Cr(III). Moreover, in plants and substrates, the Cr(III) content of the CW-MFC system was higher than that of the control, and the bioconcentration and translocation factors were 0.23 and 0.05 higher than those in the control group, respectively. Therefore, the CW-MFC system can efficiently remove Cr(VI) and promote the accumulation and transport of Cr. Microbial community diversity in the CW-MFC was significantly higher than CW. The abundance of electrogenic bacteria Geobacter and metal dissimilatory reducing bacteria Acinetobacter in CW-MFC is higher than that in CW. To summarize, the study results provide a theoretical basis for the mechanism study of Cr(VI) wastewater treatment using CW-MFC systems.